The determinants of anemia severity and BMI level among anemic women of reproductive age in Indonesia - Lea Masan; Abi Rudi; Yunida Hariyanti; Hairil Akbar; Maretalinia Maretalinia; Abubakar Yakubu Abbani (Balai Litbangkes Tanah Bumbu, 2021)
Indonesia is one developing country with vary of social and culture forms, especially in Eastern part. As the vulnerable group, women of reproductive age are still facing the malnutrition, including anemia. This study aimed to examine the determinants of severity of anemia and BMI (Body Mass Index) level among anemic women. Methods: This study used the secondary data IFLS East (Indonesia Family Life Survey East) with totally 1,021 anemic women as a sample based on sampling method of SUSENAS 2010. The sample has been chosen by multi-stage random sampling with completeness of hemoglobin, weight, and height data. The dependent variables are level of anemia and level of BMI. This study tested for the univariate, bivariate (chi-square), and multivariate (ordinal logistic regression) by using STATA software. Results: The determinants of severity of anemia are BMI (AOR 1,32), place of resident (AOR 0,73), pregnancy status (AOR 0,22), and involvement in community activity (AOR 0,64). The determinant of BMI is anemia status (AOR 0.53), place of resident (AOR 0,46), educational level (AOR 0,46), pregnancy status (AOR 7,76), breastfeeding status (AOR 2,.54), ethnicity (AOR 2,42), being a Protestant (AOR 1,62), being a Chatolic (AOR 2,31), miscarriage history (AOR 5,05), and egg consumption (AOR 1,50). Conclusions: Pregnancy status is the strongest variables related to severity of anemia and pregnancy status, breastfeeding status, and ethnicity are the strongest variables related to BMI.